Development of the E-module with Project-Based Learning for the Flat Pattern Design Course - Pepi Resmanti; Anni Faridah; Yusmerita Yusmerita; Yeka Hendriyani (Journal of Innovation in Educational and Cultural Research, 2024)
This research was motivated by the disappointing results of student projects and the perceived lack of engagement with current instructional materials in flat pattern design courses. The aim was to create a project-based learning e-module designed specifically for this field of study. The study followed Borg and Gall's (1989) research and development (RD) model. Participants consisted of three lecturers and 36 students. Data collection involved using questionnaires and evaluating student project outcomes. The results suggest that the project-based learning e-module is effective and practical in flat pattern design education, promising to improve student learning outcomes. The lecturer responses indicated a 91% rating in the "very practical" category for the e-module, while students similarly rated it at 89% in the same category. The control group showed a low N-gain value of 0.15, whereas the experimental group demonstrated a high N-gain value of 0.74. The e-modules, which employ project-based learning, effectively enhance students' psychomotor skills and engagement, aligning the curriculum with industry demands. Technology integration in the classroom paves the way for further advancements in fashion education and other fields.